Analisis Kinerja Pengering Surya Photovoltaic Thermal (PV/T) pada Kondisi Tanpa Beban - Een Tonadi; Adjar Pratoto (METAL: Jurnal Sistem Mekanik dan Termal, 2020)
The present paper is concerned with experimental study of thermal performance of a Photovoltaic/Thermal (PV/T) tray dryer. The PV/T tray dryer considered consistes of a solar cell module of 100 WP integrated with a cabinet dryer. The cabinet dryer is covered with tranparent UV plastics allowing direct heating from solar radiation The ccoling air of the solar cell is used as drying medium and circulated by solar cell powered DC fans. The experiment was performed under no load condition at different weather conditions, i.e on a cloudy day and a clear day. During the experiment, the daily average solar radiation and ambient temperature are respctively 324,7 W/m2 and 26,5oC (cloudy day) and 727 W/m2 and 27,9oC (clear day). The maximum air temperatures attained in the dryer chamber are 34,4oC (cloudy day) and 40,5 oC (clear day). There is air temperature variation among the trays, however the variation is insignificant, only at the order of 1-3oC.